Effect of Different Temperature Variations and Carbonization Duration on Characteristics of Coffee Husk Briquette - Utami, Luh Gede Gita Gowinda Mulyana; Yulianti, Ni Luh; Wirawan, I Putu Surya (Jurnal BETA (Biosistem dan Teknik Pertanian), 2022)
Coffee husks can be used as an alternative energy source which is often found in the agricultural sector as biomass waste. This research was conducted to determine the effect of different temperature variations and carbonization on the quality of coffee husk briquettes. The experimental design of this study used a factorial Randomized Block Design (RAD) with 2 (two) factors. The first factor is the cooking temperature (S) 200°C, 250°C, and 300°C. The second factor is the length of writing time (L) 30 minutes, 45 minutes, and 60 minutes. The combination of a research experiment design with 2 replications will produce 18 experimental units. Parameters observed in this study include moisture content, mass density, compressive strength, ash content, volatile matter, bound carbon, and combustion rate. In this study, the data obtained were analyzed by variance test and continued with Duncan's test if there were significant differences between treatments. The results showed that the interaction of temperature and cooking time had a significant effect on the quality parameters of the briquettes produced. The briquette treatment with the curing temperature used was 300°C and the curing time of 60 minutes (S3L3) was the treatment that produced the best quality briquettes. The characteristics of S3L3 treatment briquettes are that they have a compressive strength of 235.11 kgf/cm2, a mass density of 0.62 g/cm3, a water content of 1.67%, and a combustion rate of 0.012 g/min.